CRIMINAL ATTEMPT IN THE POLISH PENAL CODE - Nazar, Katarzyna; Palichleb, Patrycja (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose: to carry out an analysis of the provisions of Article 13, Article 14 and Article 15 of the Polish Penal Code (PC), governing the institution of criminal attempt, liability for attempted offence and active repentance. Methods: the basic method used in the analysis is the dogmatic method. Results: pursuant to Article 13 § 1 PC, the elements of criminal attempt are: the intent to commit a criminal act, the conduct directly aimed at carrying out a criminal act and the lack of accomplishment. In respect of the offender who is attempting, in accordance with the wording of Article 14 § 1 PC, the court imposes a penalty within the statutory limits provided for the offence. Article 13 § 2 PC distinguishes the so-called inept attempt, which occurs when it was impossible (for objective reasons) to commit a crime from the very beginning of the offender’s conduct, and the offender was not aware of this. The punishability of inept attempt has been limited to two cases: the absence of an object suitable for being a target of the criminal act or the use of a means that is not suitable for committing the offence. In other cases, inept attempts will remain unpunished. For an inept attempt, the offender shall be liable on a general basis (as in the skilful attempt), but the difference is that the court may apply an extraordinary mitigation of penalty or refrain from imposing the penalty. The institution of active repentance referred to in Article 15 PC gives the offender, in the stage of attempting, the legally guaranteed possibility of being unpunished if he voluntarily gives up the commission or prevents the effect which constitutes a statutory criterion of a criminal act (§1). According to § 2, the court may apply an extraordinary mitigation of penalty to the offender who voluntarily sought to prevent the effects of a criminal offence. Discussion: the most doubt arises in the context of distinguishing between the preparation and the attempt and between the skilful attempt and the inept attempt.